Innate Immune Activation by Tissue Injury and Cell Death in the Setting of Hematopoietic Stem Cell Transplantation - Brennan, Todd V.; Rendell, Victoria R.; Yang, Yiping (Frontiers in Immunology, 2015)
Allogeneic hematopoietic stem cell transplantation (Allo-HSCT) with donor lymphocyte infusion is the mainstay of treatment for many types of hematological malignancies, but the therapeutic effect and prevention of relapse is complicated by donor T-cell recognition and attack of host tissue in a process known as graft-versus-host disease (GvHD). Cytotoxic myeloablative conditioning regimens used prior to Allo-HSCT result in the release of endogenous innate immune activators that are increasingly recognized for their role in creating a pro-inflammatory milieu. This increased inflammatory state promotes allogeneic T-cell activation and the induction and perpetuation of GvHD. Here, we review the processes of cellular response to injury and cell death that are relevant following Allo-HSCT and present the current evidence for a causative role of a variety of endogenous innate immune activators in the mediation of sterile inflammation following Allo-HSCT. Finally, we discuss the potential therapeutic strategies that target the endogenous pathways of innate immune activation to decrease the incidence and severity of GvHD following Allo-HSCT.